Pengembangan Website Alumni Universitas Klabat - Reymon Rotikan, S.Kom., M.S.; Andria Wahyudi; Stevani Andolo; Arter Tendean; Prayer Mg Terok (CogITo Smart Journal, 2022)
Every higher education institution has a goal to carry out a quality educational process so as to produce quality graduates. Universitas Klabat which has been established in 1965 and has produced thousands of graduates and alumni. Alumni have an important role in developing the quality of their alma mater education, even though alumni are no longer on the Universitas Klabat campus. Some of the roles alumni can take to contribute to their alma mater include financial donations, sharing practical knowledge in the workplace to students by becoming resource persons in various academic and student activities, as well as information about job vacancies in their companies or businesses owned by alumni. . Having a website that can bring alumni together, a source of information about alumni is an unavoidable need. Therefore, in this study, a website was developed that consists of two applications, namely a portal that contains alumni news, information on alumni associations, and activities to be carried out. The second application of the results of this research is a system where alumni can register, fill in personal data in detail, interact with fellow alumni, find friends, and post information such as job vacancies. With this website, alumni can contribute, both to Klabat University as their alma mater and build networks with fellow alumni.